2014
DOI: 10.1097/qai.0000000000000295
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Benefits of Antiretroviral Therapy in Ugandan Children Aged 0–6 Years With HIV

Abstract: Background Insufficient data on neurodevelopmental benefits of antiretroviral therapy (ART) in children. Methods Prospective study of 329 mothers and children aged 0–6 years to assess neurodevelopment. Results stratified by the maternal (M) and child (C) HIV status (MHIV−/CHIV−, MHIV+/CHIV−, and MHIV+/CHIV+). Gross Motor, Visual Reception, Fine Motor, Receptive and Expressive Language scores assessed by Mullen Scales of Early Learning. Global cognitive function was derived from an Early Learning Composite sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
3
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 38 publications
4
34
3
1
Order By: Relevance
“…Previous studies have found deficits in language in HIV-infected children [25, 2830]. We previously reported that use of LPV/r-based ART was associated with earlier age for speech in this cohort.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have found deficits in language in HIV-infected children [25, 2830]. We previously reported that use of LPV/r-based ART was associated with earlier age for speech in this cohort.…”
Section: Discussionsupporting
confidence: 52%
“…Research from high-income countries suggests that children treated with a protease inhibitor (PI) based antiretroviral (ARV) regimen have normal global cognition scores [4] and that ARV treatment duration is associated with a reduction in neurological impairment [5]. However, evidence is largely limited to subtype-B, which is responsible for only 11% of global HIV infections [6].…”
Section: Introductionmentioning
confidence: 99%
“…Using this approach, Laughton and colleagues documented in a randomized controlled trial that very early initiation of treatment with HAART among South African children with HIV resulted in better neurodevelopmental outcomes [11]. The same seems to be true in an observational study of very young Ugandan children [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Although long-term effects of ART in young children living in rural Uganda have been associated with better neurodevelopmental outcomes [23], no studies to date have examined whether being on ART affects working memory.…”
Section: Introductionmentioning
confidence: 99%